(untitled) (Damascus University Journal of agriculture sciences, 2021)
The research was carried out at Biological Control Department in Lattakia, during 2017 on Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae). The genetic improvment line of fecundity was done for twelve generations of cross-breeding and compared with the control line. The numerical changes of the quantitative traits (QTs) were studied across the generations and according to the improvement tested line in comparison with control line in order to determine the effect of fecundity genetic line. The studied quantitative traits were (length of females, fecundity, reproductive, survival rate , preying potential of the 3rd larval instar, preying potential of female, larval period , developmental period and sex ratio( and estamated for each selection cycle in (F3, F6, F9, F12). Statistical analyses of the fecundity line showed significant increases of the value of fecundity from148.13±37.03 in Po to 232.80±27.70 in F9 and insignificant differences between F9 and F12, While insignificant differences between Po and F9 in the control line then significant decrease between F9 and F12 and were 133.33±35.12, 119.80±31.96 respectively. The selection line contributed to raise the values of traits (length of the female, reproduction and survival rate) and increased significantly from (4.68± 0.33, 132.73 ±38.87, 88.82±5.83) in Po to (4.98±0.17 mm, 227.53±27.40, 94.53±2.21) in F12, respectively. while there were no significant differences in all other quantitative traits; (preying potential of the 3rd larval instar, preying potential of female, larval period , developmental period and sex ratio(, during the studied generations. Fecundity parameter response to selection recorded 62.31% in the fecundity line and -19.13% in the control